Paediatric reproducibility limits for the forced expiratory volume in 1 s. Issue 10 (11th August 2020) - Stanojevic, Sanja; Filipow, Nicole; Ratjen, Felix
Abstract : Background: Current reproducibility standards for spirometry were derived using a small adult dataset and may not be optimal for interpretation of repeated measurements of lung function in children. Objective: To define reproducibility limits for forced expiratory volume in 1 s (FEV1 ) change that represent the normal within-subject between-visit variability in healthy children and evaluate these limits as a tool to monitor children with cystic fibrosis (CF). Methods: Repeated FEV1 measurements (3 months to 5 years apart) from healthy children from the Global Lung Function Initiative data repository were used to derive a conditional change score. Spirometry and clinical data from a CF clinical database was used to verify utility in clinical practice. Results: A reproducibility change score was derived from 47 938 FEV1 measures from 7885 healthy children 6–18 years of age. The simple algorithm, which is conditional on the initial measurement, also accounts for age and time interval between measurements. The change score limits of reproducibility were much narrower than currently used cut-offs. Specifically, changes, considered as improvements using either a 12% or 10% relative change from baseline, are too wide for children. In CF, there was overall agreement between different approaches, with the distinct advantage that the change score was not biased by regression to the mean. Conclusions: Compared with current approaches to interpretation of repeated lung function measurements, the proposed change score was less biased and provides a simple alternative to reduce misinterpretation.